Comparison of continuous subcutaneous insulin infusion treatment and multiple daily injection treatment on the progression of diabetic complications in Japanese patients with juvenile‐onset type 1 diabetes mellitus. Issue 9 (19th May 2022) - Masuda, Takafumi; Katakami, Naoto; Taya, Naohiro; Miyashita, Kazuyuki; Takahara, Mitsuyoshi; Kato, Ken; Kuroda, Akio; Matsuhisa, Munehide; Shimomura, Iichiro
ABSTRACT: To evaluate whether continuous subcutaneous insulin infusion attenuates the progression of diabetic complications, we retrospectively extracted data from 35 individuals who had developed type 1 diabetes mellitus aged ≤20 years and whose treatment had been changed from multiple daily injections to continuous subcutaneous insulin infusion. The annual changes in estimated glomerular filtration rate, urinary albumin excretion rate, carotid intima‐media thickness and brachial‐ankle pulse wave velocity during each treatment period were calculated. Although mean glycated hemoglobin under the continuous subcutaneous insulin infusion treatment was lower than that under the multiple daily injection treatment, there were no significant differences in annual changes in diabetic nephropathy and atherosclerosis between the two treatment periods. This pilot study showed that, in Japanese patients with juvenile‐onset type 1 diabetes mellitus, there was no significant difference in the progression of diabetic nephropathy and atherosclerosis, at least in the early stage, between the two treatments. Abstract : To evaluate whether continuous subcutaneous insulin infusion attenuates the progression of diabetic complications, we retrospectively extracted data from 35 individuals who had developed type 1 diabetes mellitus under 20 years of age and whose treatment had been changed from multiple daily injections to continuous subcutaneous insulin infusion. Although mean glycated hemoglobin under the continuous subcutaneous insulin infusion treatment was lower than that under the multiple daily injection treatment, there were no significant differences in annual changes in diabetic nephropathy and atherosclerosis between the two treatment periods. This pilot study indicated that, in Japanese patients with youth‐onset type 1 diabetes mellitus, there was no significant difference in the progression of diabetic nephropathy and atherosclerosis, at least in the early stage, between the two treatments.